Isolation of Salmonella spp. from raw meat, elucidation of their antibiotic susceptibility pattern and evaluation of the antimicrobial efficacy of Oregano (Origanum vulgare) and Black Sesame (Sesamum indicum) - Moumi, Sunayna Hossain (BRAC Univeristy, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Biotechnology, 2018.